Construction of cubic Ball surface based on biharmonic partial differentiation equation - Saaban, A. (American Institute of Physics Inc., 2014)
This paper will discuss a new method of Ball surface generation from prescribed boundaries based on the partial differential operator. In particular, we focus on the construction of a bicubic Said-Ball surface using biharmonic partial differentiation equation. The main result is that the use of biharmonic Said-Ball surface would enable the overall surface to be generated and controlled based on the boundary curves rather than a set of control points. We illustrate the new method by using several graphical examples. Â© 2014 AIP Publishing LLC.